Biomarkers reveal the role of photic zone euxinia in exceptional fossil preservation: An organic geochemical perspective - Melendez, Ines; Grice, Kliti; Trinajstic, Kate; Ladjavadi, Mojgan; Greenwood, Paul; Thompson, Katharine (Geological Society of America, 2013)
Photic zone euxinia (PZE) has proven important for elucidating biogeochemical changes that occur during oceanic anoxic events, including mass extinction and conditions associated with unique fossil preservation. Organic geochemical analyses of a 380 Ma invertebrate fossil, which included well-preserved soft tissues, from the Gogo Formation (Canning Basin, Western Australia) showed biomarkers and stable isotopic values characteristic of PZE and a consortium of sulfate-reducing bacteria, which lead to exceptional fossil and biomarker preservation. The carbonate concretion contained phytoplankton, green sulfur bacteria (Chlorobi), and sulfate-reducing bacteria biomarkers with an increasing concentration toward the nucleus where the fossil is preserved. The spatial distribution of cholestane unequivocally associated with the fossilized tissue and its high relative abundance to the total steranes suggest that the fossil is a crustacean. The presence of an active sulfur cycle in this Devonian system, including sulfate reduction and the resulting PZE, played a pivotal role in the preservation of soft tissue from the fossil and its associated low-maturity biomarker ratios.